Pengembangan Sistem Informasi Rekrutmen Anggota Organisasi berbasis Web dengan Pemberitahuan dan Konfirmasi Memanfaatkan Simple Mail Transfer Protocol (SMTP), SMS, dan Whatsapp Gateway (Studi Kasus Universitas Brawijaya) - Abdullah Harits; Bayu Rahayudi; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The many kinds of organizations within Universitas Brawijaya make students as registrants have many options to register as members in it. However, many choices are not supported by system-centric information. Information that is not centralized also makes the target number of registrant members in an organization not achieved. This causes students not to be aware of the various types of organizational recruitment available in the environment and the selection results obtained are not good, because the large number of applicants affects the results of the members obtained (Garaika & Margahana, 2019). In the recruitment process there is also registrant data. Disorganized registrant data in hardfile and softfile form allows errors in its management (Gata, Prabowo & Kusuma, 2017). In addition, the HR department continues to provide notification of information regarding the recruitment process to applicants one by one. This method is a method that is less effective because it takes a lot of time. Therefore, the authors conducted research on the development of a web-based information system that can be used to (1) provide member recruitment information, (2) manage registrant data, (3) notification and confirmation to registrants automatically using SMTP, SMS, and Whatsapp gateways. , (4) obtaining information, and (5) completing registrant data forms during the recruitment process for organizational members. This study uses 2 methods, namely data collection methods and system development. The data collection method is done by literature study, interview, questionnaire, and observation. The system development method uses the waterfall model which starts from needs analysis, design, implementation and testing. Tests carried out using white box and black box on the functions built and all of them are valid. This research produces an information system on the recruitment of organizational members in Universitas Brawijaya which can be useful for both organizations and students in the recruitment process of organizational members.